Fiscal Issues in the New EU Member Countries: Prospects and Challenges - Helmut Wagner (SUERF - The European Money and Finance Forum, 2006)
This paper examines the fiscal challenges that the new EU member states in Central and Eastern Europe (NEW-8) are facing that arise from both EU membership and from developments that are essentially independent of EU membership. While the direct fiscal strains caused by EU membership may appear to be only short term and of minor importance, they are more challenging when regarded in the context of the impact on the NEW-8 of globalization (locational competition) and country-specific structural characteristics. It is argued that there is an urgent need for fiscal reforms in these countries that requires both determination with respect to restructuring the budget and innovativeness in regard of increasing the efficiency of public spending and collecting tax revenues. Several reform options are discussed.
Keywords: H5; H6; P2; 330; European integration; fiscal challenges; Finanzpolitik; Finanzreform; Öffentlicher Haushalt; EU-Mitgliedschaft